Deja review: Obstetrics and Gynecology - Miller, Emily S.; Lee, Catherine J. (New York : McGraw-Hill Medical, 2011)
"Flashcards in a book" provide a comprehensive yet concise review for the obstetrics and gynecology clerkship. Maximum retention in minimum time! Drawn from the perspective of residents fresh from their medical school and USMLE experiences, these unique "flashcards in a book" help you remember high-yield facts in the least amount of time possible and focus on what is essential for success on the shelf exam and the USMLE Step 2 CK. Active recall Q&A boils down must-know concepts for clerkship success. Clinical vignettes appear at the end of each chapter. Mnemonics and key words help you focus on core facts. Complements larger course books and works well with other type of review books. Convenient 6"x9" size is great for study on the go. The content you need for clerkship success"--Provided by publisher.
Catherine J. Lee is first named author on previous ed.
Includes index.
Keywords: Gynecology -- Examinations, questions, etc; Obstetrics -- Examinations, questions, etc; Obstetrics -- Examination Questions; Female Urogenital Diseases -- Examination Questions; Gynecology -- Examination Questions; Pregnancy Complications -- Examination Questions